The speed of adjustment towards optimal capital structure in Indonesia: a test of dynamic trade-off model - Wendy,; Salim, Kevin Christanto (Penerbit Universiti Kebangsaan Malaysia, 2019)
Capital structure remains to be a highly debated topic and the number of researches on the dynamic version of capital structure in Indonesia is very small. Besides, the inclusion of macroeconomic factors is even harder to locate. This paper analyzes the financing behaviour of non-financial firms in Indonesia. The objective is to measure the adjustment speed of the firms toward the optimal capital structure. Partial Adjustment Model (PAM) was used to analyzed the data. It is expected that non-financial firms in Indonesia possess a target leverage and make partial adjustments toward the target over time. The empirical findings from 250-panel data observation revealed that tangibility and firm’s size had a positive and significant relationship with target leverage. In addition, macroeconomic variables (GDP growth and inflation rate) were found to be negatively correlated with the firm’s speed of adjustment. Finally, the result shows that non-financial firms in Indonesia readjusted toward their target leverage at a speed rate of approximately 57.44% a year. These evidences conclude that the financing behaviour of non-financial firms in Indonesia tended to follow the dynamic trade-off theory.